If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7x+7(x-2)=56
We move all terms to the left:
7x+7(x-2)-(56)=0
We multiply parentheses
7x+7x-14-56=0
We add all the numbers together, and all the variables
14x-70=0
We move all terms containing x to the left, all other terms to the right
14x=70
x=70/14
x=5
| 11x-5=12x-11 | | 2x+4x=8x+10 | | 11x–5=11x–5 | | 11t–5=11t–5 | | 2+-x=15 | | 1/5x+5=12 | | 4x+27=3x+49 | | F(x)=14-0.5×30 | | -7=5+u/2 | | .5(r+2.5)=3 | | 9/7=-2/b | | 2q+10=12 | | 2x+3=-3x-12 | | 24=14y-8 | | 5/3x+-4/3x+-1=8 | | 21y=-42 | | 31.25(p+5)=750 | | 6x-(7)=13+2x | | 7c-2c+2c-2c=5 | | 15q-11q-3q=17 | | 8h+18h+-16h+-6h+13h=-17 | | 20q-18q+2q+q-q=16 | | 3x-15=2x(x-5) | | -5(1+m)=-5-4m | | 17v-17v+2v=14 | | a+4a+3a-5a=6 | | I3xI=18 | | 7x+x-4x-x-2x=19 | | 16u-15u=8 | | 16u-15=8 | | 17u-15u=10 | | 9=4p+3p |